'UNSINKABILITY' OF IRON-MANGANESE NODULES AND SOME PROPERTIES OF THE BOTTOM LAYER OF THE OCEAN - Barenblatt G.I.; Baturin G.N.; Brekhovskikh L.M. (My University, 1989)
The question as to the origin of iron-manganese nodules, which are currently the principal type of solid mineral that could be mined in the ocean (with a total reserve of about 1012 tons, has both geological-geochemical and physical aspects. One of these aspects involves the enigmatic 'unsinkability' of the nodules, which, according to radiometric and other measurements, grow at a rate an average of 3 orders of magnitude slower than the rate of accumulation of the underlying sediments. However, despite their greater density, the nodules remain on the surface of the unconsolidated sediments for long periods of geologic time. The authors attribute the unsinkability of the nodules to the hydrodynamic properties of the density-stratified bottom layers of the ocean. A mathematical model is presented to explain this phenomena. Finally, the unsinkability of nodules may also be attributed to their agitation by tidal flow components, which have also been detected in the bottom layer. The development of a high-velocity bottom layer may give rise to numerous phenomena associated with the development of high-energy eddy structures in the flow. Such structures have been observed in bottom flows at a frequency of about 10-6 sec; uplift of particles and clarification of the flow have been observed directly under these conditions.